DETERMINANT OF BANK MUAMALAT’S PROFITABILITY BASED ON FINANCIAL VARIABLES - Rachmawaty, Rachmawaty; Irawan, Panji; Jati, Waluyo (Al-Infaq: Jurnal Ekonomi Islam, 2023)
Bank Mualamat is Indonesia's first Islamic Bank, founded in 1991. In its journey, Bank Muamalat experienced a crisis, including in 2015-2019, related to the Capital Adequacy Ratio (CAR), which was close to the minimum limit, Non-Performing Financing (NPF), which was high above the industry average Banking and ended with low profitability. This study focuses on determining the financial variables that affect the profitability of Bank Muamalat. The financial variables tested were CAR and Net Income Margin (NIM), Financing to Deposit Ratio (FDR), and NPF to Profitability (ROA) for the 2011-2022 period. The results of this study partially show that CAR and FDR do not affect ROA, but NIM and NPF significantly affect ROA. The research results that the Management of Bank Muamalat must consider are that simultaneously, CAR, NIM, FDR, and NPF affect ROA with a significance value of 0.012 <0.05. Based on the analysis, the coefficient of determination is 89.4%, which means that CAR, NIM, FDR, and NPF have an effect of 89.4% on ROA.